Injection molding of tungsten powder treated by jet mill with high powder loading: A solution for fabrication of dense tungsten component at relative low temperature. (January 2017) - Li, Rui; Qin, Mingli; Liu, Chengcheng; Huang, Hua; Lu, Huifeng; Chen, Pengqi; Qu, Xuanhui
Abstract: The greater demands on final product quality of powder metallurgy processing have led to an increased demand for metal powders with high quality. In this paper we report the successful preparation of tungsten powder with a near-spherical shape and surface morphology by jet milling process, with the disappearance of agglomeration and the improvement of dispersion, narrow particle size distribution of tungsten powder was achieved. The values of D10, D50 and D90 changed from 2.02 μm, 3.67 μm and 6.34 μm to the original tungsten powder to 1.36 μm, 2.13 μm and 3.19 μm for the treated tungsten powder, respectively. The process increases apparent density and tap density from 3.71 g/cm3, 5.54 g/cm3 to 5.71 g/cm3, 8.47 g/cm3. Due to the optimization of the powder characteristics, the powder loading of the feedstock was raised to 65 vol% for the treated powder. The sintered samples of 65 vol% powder loading is easy to get sinter densification with no cracks and has superior hardness and microstructure at a relative low temperature of 1900 °C. Highlights: Jet milling process significantly changed the tungsten powder characteristics. The high powder loading of the feedstock has been obtained. Tungsten sample is easy to get sinter densification at relative low temperature.